2001
DOI: 10.1016/s0002-9440(10)64097-7
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage-Specific Matrix Protein Chondromodulin-I Is Associated with Chondroid Formation in Salivary Pleomorphic Adenomas

Abstract: Chondromodulin-I (ChM-I) is a novel cartilage-specific matrix protein. In the growth plates of the long bones, ChM-I was shown to be expressed in mature to upper hypertrophic chondrocytes, and to be deposited in the cartilage matrix. As ChM-I strongly inhibits angiogenesis, cartilage is avascular. Also, ChM-I has bifunctional activity against chondrocyte proliferation. On the other hand, pleomorphic adenomas of the salivary glands frequently have chondroid elements. To elucidate the relationship between chondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…Aggrecan deposition was also seen in myxoid and chondroid stroma of salivary pleomorphic adenomas, whereas type II collagen deposition was observed in only chondroid stroma of pleomorphic adenomas. 5,6,22 Histochemically, toluidine blue stain also showed marked metachromasia of the stroma. The matrix nature of matrix-producing carcinoma of the breast was similar to that of salivary pleomorphic adenomas and normal cartilage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Aggrecan deposition was also seen in myxoid and chondroid stroma of salivary pleomorphic adenomas, whereas type II collagen deposition was observed in only chondroid stroma of pleomorphic adenomas. 5,6,22 Histochemically, toluidine blue stain also showed marked metachromasia of the stroma. The matrix nature of matrix-producing carcinoma of the breast was similar to that of salivary pleomorphic adenomas and normal cartilage.…”
Section: Discussionmentioning
confidence: 94%
“…3 This macromolecule deposits in the hypertrophic zones of growth plate cartilage, 4 although it was reported to deposit in the salivary pleomorphic adenoma, which frequently showed mesenchyme-like elements, including myxoid and chondroid tissues. 5,6 Type II collagen, which is a cartilage-specific major collagen, and chondromodulin-I (ChM-I), which is cartilage-specific noncollagenous matrix protein, 4,7,8 are deposited in the normal cartilaginous matrix. These molecules can be useful markers of cartilaginous differentiation.…”
mentioning
confidence: 99%
“…Factor VIII is a marker for endothelial cells used to evaluate angiogenesis, 21 and bFGF is a proangiogenic factor in adenomas as well as adenocarcinomas. 22 Immunostaining for Factor VIII on control and EGCG-treated small intestinal tumors suggested that endothelial-lined capillaries were more prevalent in the control group, compared with EGCG-treated tumors ( Figure 5D, bottom). Finally, ELISA assay was performed using the small intestinal tissue samples from the respective 3 groups, and results showed significant suppression of bFGF by EGCG (P < .05) compared with controls using the Dunnett test ( Figure 5E).…”
Section: Effects Of Bfgf On Intestinal Tumorigenesis In Apc Min/+ Micementioning
confidence: 98%
“…As binding between fibroblast growth factor (FGF) and FGF receptor-1 was reported to inhibit terminal differentiation of chondrocytes and calcification in vitro [12], we have reported that co-expression of FGF-2 and FGF receptor-1 in lacuna cells may play an essential role in the inhibition of ossification of the chondroid element in pleomorphic adenomas [14]. Although FGF-2 is also known to be a strong angiogenic factor [2,5,20], pleomorphic adenoma is a hypovascular tumor, due to the low density of CD34-positive endothelial cells [16]. Cartilage-specific matrix protein, bovine chondromodulin-I (ChM-I), has been shown to be a strong inhibitory factor against angiogenesis in vitro [8,9], and human ChM-I has also been cloned [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cartilage-specific matrix protein, bovine chondromodulin-I (ChM-I), has been shown to be a strong inhibitory factor against angiogenesis in vitro [8,9], and human ChM-I has also been cloned [10]. Recently, using an immunohistochemical technique, we have shown that ChM-I is deposited in the inter-territorial matrix of the chondroid element of pleomorphic adenoma [16]. As ChM-I serves as a barrier against the angiogenic property of FGF-2, pleomorphic adenomas are hypovascular tumors.…”
Section: Introductionmentioning
confidence: 99%